Older Adults' Behavior Intentions Once a COVID-19 Vaccine Becomes Available. (September 2021) - Callow, Michael A.; Callow, Daniel D.
Background: The purpose of this study was to examine the impact of antecedent variables on older adults' intention to get a CORONAVIRUS DISEASE-2019 vaccine. Older adults are at higher risk of severe illness from the disease and face an increasingly ageist general population who misrepresent the pandemic as an older adult problem. We use the Theory of Planned Behavior framework to examine vaccine behavior intention. Method: A convenience sample ( n = 583) of adults aged 60 and older in the United States participated in an online survey using vignettes. Hierarchical regression and analysis of covariance were used to test our model. Results: Results suggest that perceived risk of the pandemic, general vaccine beliefs, and political affiliation influence respondents' attitude toward the vaccine. Respondents' attitudes toward the vaccine and their physician's recommendation help shape vaccine intention. Conclusion: The results provide partial support to the proposed model in shaping vaccine intention among older adults.